Impact of COVID-19 on Youth With ADHD: Predictors and Moderators of Response to Pandemic Restrictions on Daily Life. Issue 9 (July 2022) - Rosenthal, Eliana; Franklin-Gillette, Sara; Jung, Hi Jae; Nelson, Amanda; Evans, Steven W.; Power, Thomas J.; Yerys, Benjamin E.; Dever, Bridget V.; Reckner, Erin; DuPaul, George J.
We examined COVID-19 symptoms and infection rates, disruptions to functioning, and moderators of pandemic response for 620 youth with ADHD and 614 individually matched controls (70% male; M age  = 12.4) participating in the Adolescent Brain and Cognitive Development study. There were no group differences in COVID-19 infection rate; however, youth with ADHD were more likely to exhibit COVID-19 symptoms ( d  = 0.25), greater sleep problems ( d  = −0.52), fear and negative emotions to infection risk ( d  = −0.56), trouble with remote learning ( d  = −0.54), rule-breaking behavior related to COVID-19 restrictions ( d  = −0.23), family conflict ( d  = −0.13), and were less prepared for the next school year ( d  = 0.38). Youth with ADHD were less responsive to protective environmental variables (e.g., parental monitoring, school engagement) during the pandemic and may need more specialized support with return to in-person schooling and daily activities.